Incompleteness in filling out the tuberculosis notification form among indigenous people in Rondônia (Research, Society and Development, 2025)
Introduction: Notification of tuberculosis is essential for epidemiological surveillance, especially among vulnerable populations such as Indigenous people. Objective: To assess the incompleteness of TB notification among Indigenous people in Rondônia - Brazil. Method: A descriptive epidemiological study with a quantitative approach, based on tuberculosis records stratified by age group (child, adolescent, adult, and elderly) in the Notifiable Diseases Information System from 2008 to 2020 and incompleteness was assessed using percentage variation. Results: 305 TB cases were analyzed. Among the mandatory variables, two were more than 50% incomplete in all age groups: sensitivity test (75.43%) and transfer destination (100%). Among the essential variables, there was an incompleteness between 20% and 50% in the 6th month of sputum smear microscopy and the occupation variable. Conclusion: Incompleteness was predominated among the variables entered after 2014 and the essential variables were identified as crucial for epidemiological calculations and the organization of case management.